Assessment of urgent investigative images transfer effectiveness from trauma and orthopaedic to neurosurgery department: a quality improvement project - Kanthan Theivendran; Marwa Khan; Tahir Khaleeq (BMJ Open Quality)
Background Neurosurgical emergencies, including cauda equina syndrome, traumatic spinal cord injuries and traumatic brain injuries, require timely diagnosis and intervention to prevent severe morbidity and mortality. Delays in these cases often stem from inefficiencies in transferring investigational images from district hospitals to external neurosurgery units.Aims This quality improvement project aimed to reduce image transfer time at Sandwell and West Birmingham Hospitals Trust (SWBH) to the Queen Elizabeth Hospital Birmingham neurosurgery unit. It sought to empower Trauma and Orthopaedics (T&O) doctors to independently transfer images using an image exchange portal (IEP) software, bypassing reliance on traditional picture archiving and communication teams.Methods Over three Plan-Do-Study-Act cycles (February and September 2024), T&O registrars and junior doctors were trained to use the IEP. Additional instructional resources were provided following low compliance. Image transfer times and neurosurgical response times were compared preintervention and postintervention.Results The intervention reduced the average time from referral to image transfer from 18 hours to 3.6 hours across the cycles. The proportion of images transferred within 1 hour increased from 36% to 59%, and 87% of images were reviewed by neurosurgery within 6 hours by the final cycle. Operational cost savings were achieved by reducing reliance on IT services, radiographers and length of stay.Conclusions This project improved the timeliness of image transfer and neurosurgical care at SWBH. Although IEP software proved effective locally, its broader applicability across UK hospitals remains uncertain. The findings highlight the need for a national solution to streamline image transfers and further research to enhance technologies supporting rapid investigative imaging. Empowering front-line clinicians with appropriate tools provides a replicable model for addressing similar challenges in other institutions.